Metaphor effects and History of Education (Foro de Educacion, 2017)
This article calls into question the problem of teaching History of Education in a time of a symbolic crisis, weak hermeneutics and hegemony of skill-oriented culture. Three basic notions sustain this research project: effects of metaphor, genealogy and archive. In order to know the past we need to ask for it from within the present. We must undo the fictious continuity of an incomplete, partial, multiple and plural tradition in order to introduce some effects of metaphor in the educational discourse on History. Following the statements of Lacan, Foucault, Blumenberg and Gadamer we analize an experience of teaching History of Education with students in their first year of Teaching College.